Recruitment of general practices: Is a standardised approach helpful in the involvement of healthcare professionals in research? - Riis, Allan; Jensen, Cathrine E; Maindal, Helle T; Bro, Flemming; Jensen, Martin B (SAGE open medicine, 2016)
Introduction: Health service research often involves the active participation of healthcare professionals. However, their ability and commitment to research varies. This can cause recruitment difficulties and thereby prolong the study period and inflate budgets. Solberg has identified seven R-factors as determinants for successfully recruiting healthcare professionals: relationships, reputation, requirements, rewards, reciprocity, resolution, and respect. Method: This is a process evaluation of the seven R-factors. We applied these factors to guide the design of our recruitment strategy as well as to make adjustments when recruiting general practices in a guideline implementation study. In the guideline implementation study, we studied the effect of outreach visits, quality reports, and new patient stratification tools for low back pain patients. Results: During a period of 15 months, we recruited 60 practices, which was fewer than planned (100 practices). In this evaluation, five of Solberg’s seven R-factors were successfully addressed and two factors were not. The need to involve (reciprocity) end users in the development of new software and the amount of time needed to conduct recruitment (resolution) were underestimated. Conclusion: The framework of the seven R-factors was a feasible tool in our recruitment process. However, we suggest further investigation in developing systematic approaches to support the recruitment of healthcare professionals to research.